Athlete and coach agreement: Identifying successful performance - Millar, S.-K.; Oldham, A. R. H.; Renshaw, I.; Hopkins, W. G. (International Journal of Sports Science & Coaching, 2017)
Traditional coaching views the coach as an informed resource and the athlete as a reflection of expert knowledge. Recent approaches have criticised a strictly coach driven model of expertise, and in doing so have acknowledged the unique and developing knowledge of athletes, which emerges from extended practice. The growth of the athlete`s contribution in the coach-athlete dyad invites interesting questions about the usefulness of athlete knowledge and the changing role of the coach. Athlete-coach agreement was assessed via a triangulation of quantitative boat speed data from a single sculler and matched to phases of successful rowing that rowers and coaches both agreed on. Coach and rower were able to identify when the boat was travelling its fastest or slowest. However, when the performance was marginally faster or slower, they disagreed, and generally the rowers were more accurate about the performance than their coach. Implications for contemporary coaching practices are considered. ABSTRACT FROM AUTHOR